2007
DOI: 10.1248/bpb.30.1226
|View full text |Cite
|
Sign up to set email alerts
|

.ALPHA.1-Acid Glycoprotein Suppresses Rat Acute Inflammatory Paw Edema through the Inhibition of Neutrophils Activation and Prostaglandin E2 Generation

Abstract: a 1 -Acid glycoprotein (AGP), a member of the lipocalin family, is a polypeptide containing 2 disulfide bonds and 5 carbohydrate chains, the latter of which account for about 40% of its total mass of 40 kDa.1-4) The half-life of 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…29,35 Orosomucoid is also bound to the surface of cultured bovine pulmonary microvascular endothelial cells. 36 It has been found that orosomucoid modulates the transport of charged solutes across the wall of peripheral and cerebral microvessels in vivo by decreasing the transport of negatively charged molecules but increasing that of positively charged ones, 13,23,46 suggesting that orosomucoid plays an essential role in maintaining the permeability property of endothelium by adding negative charge to the SGL.…”
Section: Introductionmentioning
confidence: 99%
“…29,35 Orosomucoid is also bound to the surface of cultured bovine pulmonary microvascular endothelial cells. 36 It has been found that orosomucoid modulates the transport of charged solutes across the wall of peripheral and cerebral microvessels in vivo by decreasing the transport of negatively charged molecules but increasing that of positively charged ones, 13,23,46 suggesting that orosomucoid plays an essential role in maintaining the permeability property of endothelium by adding negative charge to the SGL.…”
Section: Introductionmentioning
confidence: 99%
“…3) We have seen that thalidomide acts at different levels of regulation and there are reports of this molecule acting at the very fundamental level of DNA. A very recent in situ electrochemical and atomic force microscopy (AFM) study of thalidomide-DNA interaction has been reported by Oliveira et al (2009) [145]. The main findings of the study convey that, thalidomide interacts specifically with the dsDNA by intercalating between the bases and inducing structural changes in B-DNA, in a time-dependent manner.…”
Section: Other Mechanisms Involved In the Inhibition Of Tnf-by Thalidmentioning
confidence: 96%
“…Interestingly, thalidomide is seen to have specific interaction with GC-rich promoter sequences [96]. Reports convey that, thalidomide can regulate the GC-rich promoter of vascular endothelial growth factor (VEGF) and also down regulate the basic fibroblast growth factor (bFGF) expression in glioma cells [145]. Drucker et al(2003) and group showed that thalidomide down regulates transcription levels of GC-rich promoter genes in multiple myeloma (MM) [146].…”
Section: Other Mechanisms Involved In the Inhibition Of Tnf-by Thalidmentioning
confidence: 99%
“…Alpha-(1)-acid glycoprotein (AGP) (normal range=0-130 ng/ml), an acute-phase protein, was measured on days 0 (preoperative), 7 and 14 (19).…”
Section: S Aureus Strains and Infection Processmentioning
confidence: 99%